Fine roots dynamics in a Mediterranean forest: effects of drought and stem density (Tree Physiology, 1998)
Summer drought is a characteristic trait of Mediterranean climates and can limit primary production. The holm oak (Quercus ilex L.) forest at the Prades Experimental Complex of Catchments (PECC, NE Spain) was managed by clearcutting until the 1950s. As a result of this practice, the forest has a high density (13000 stems ha−1) that is causing growth stagnation and intense competition for water. A thinning experiment was conducted to release resources, reduce stem competition and improve forest productivity. Minirhizotrons were installed in two plots in each of the thinned and control stands and fine root dynamics quantified to a soil depth of 60 cm over a 2-year period (June 1994–May 1996).Soil water content was higher and soil water penetrated deeper in the soil (30–50 cm) in the thinned plots than in the control plots. In the control plots, soil temperature did not vary substantially with depth (mean = 11.65 °C), whereas soil temperature was higher in shallow horizons compared with deep horizons in the thinned plots. Mean soil temperature was one degree higher in the thinned plots than in the control plots (12.9 versus 11.9 °C). There were always more roots in the top 20 cm of soil in thinned plots than in control plots. In the thinned plots, more than 50% of root density (root no. cm−2) was located in the top 20 cm of soil, whereas root density never reached 50% in the 0–20 cm soil layer of the control plots. Roots longevity varied from 35 to 471 days, and there were significant differences between soil depths. Root longevity was greater in the control plots than in the thinned plots.
10.1093/treephys/18.8-9.601